Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Peru: Social Issues and Comedy in Fiction - Cassano, Giuliana; Vásquez, Guillermo; Dettleff, James A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
The country’s political crisis led to the confrontation between the Peruvian Congress and President Martín Vizcarra on irreconcil- able limits. After a second denial of confidence, Vizcarra made use of his constitutional prerogatives and dissolved Congress at the end of September 2019. The majority of the mass media step in line with the different positions of the Executive or the opposition, giv- ing much more attention to the political situation, thus modifying the TV programing. In this scenario, the Enfoca group – owner of Latina station – has continued looking for potential buyers, but without success yet. The conglomerate – with interest in financial, health and productive sectors – does not feel that the investment made in acquiring all the station’s shares seven years ago yielded the expected results. Meanwhile, Willax – a small locally held station acquired by the Wong group in 2015 with promises of a large investment – has become a stronghold of opposition to the government of Vizcarra and the largest broadcaster of Korean fictions. In February 2020, they an- nounced that a commercial partnership had been signed with South Korean company CJ ENM, a production company of several Korean dramas and the award-winning film Parasite, but without indicating what this company could mean for audiovisual production in Peru.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Pérou (corpus analysé); Pérou (lieu de production du savoir); _Nettoyé

Brazil: Time of Brazilian Streaming - Vassallo de Lopes, Maria Immacolata; Prezia Lemos, Ligia (Obitel 2020: Melodrama in Times of Streaming, 2020)
In 2019, the World Wide Web (www) celebrated its 30th anni- versary, However, the internet had not yet asserted itself as a right in the “network society” (Castells, 2009), and its balance points to the expansion of both opportunities and threats. Another fact that deserves to be highlighted in the year was the drop in the rating as a global phenomenon that challenges the television industry. It means change of habits and search for new business models. The integration of platforms and the generation of quality content appear as pillars of thetransformation of audiovisual worldwide. And the changes are manifested with a certain degree of diversity, according to the economic and cultural characteristics of each society, with disruptive processes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé

Argentina: The Fall of Open TV Continues: Production Companies Bet on Platforms with Themes Regarding Marginality and Corruption - Aprea, Gustavo; Kirchheimer, Mónica S.; Rivero, Ezequiel A. (Obitel 2020: Melodrama in Times of Streaming, 2020)
Serial fiction released in Argentina in 2019 continues to fall. Only one telenovela had more than 200 chapters. To a lesser extent than the previous year, the supply of serialized fiction incorporated themes from the social agenda, especially feminist struggles and the visibility of sexual dissidence. The channels found in the co-produc- tion and in the production for platforms one of the ways in which fic- tion survives. Some of these programs are now on the open television screen. New fiction releases from Ibero-America are also falling.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; Argentine (corpus analysé); Argentine (lieu de production du savoir); _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Cuerpos in/a-propiados: carte-de-visite y las nuevas ciudadanias en la pardocracia venezolana postindependentista - González-Stephan, Beatriz (Memoria y Sociedad, 2013)
En medio del proceso de construcción de la República, durante el siglo xix, en Venezuela los sectores no blancos de la sociedad intentaron legitimarse a través de la fotografía en las carte-de-visite, con el objetivo de ratificar su posición en esta sociedad ‘café con leche’. El uso de esta tecnología, así como la aparición y aceptación de manuales de urbanidad, fueron parte de un proceso en el que estos sectores intentaron ‘modernizarse’, reflejando las tensiones sociales asociadas, por ejemplo, a la dicotomía campo-ciudad o a la necesidad de ‘blanquearse’ ante los ojos de los coterráneos. El objetivo de este trabajo, es estudiar la manera en que el retrato fotográfico y el manual de urbanidad actúan en una sociedad cuyas diferencias y distancias sociales y económicas han sufrido un gran trastorno luego del proceso independentista. During the process of the construction of the Republic, in the 19th Century, non-white sectors of Venezuelan society attempted to legitimise themselves through photographs in their cart-de-visite, with the object of ratifying their position in this ‘coffee and milk’ society. The use of such technology, as well as the introduction and acceptance of urbanity handbooks, were part of a process in which these sectors tried to ‘modernise’, reflecting related social tensions, for example, the urban-rural dichotomy or the need for ‘whitening’ themselves in the eyes of their fellow citizens. The purpose of this paper is to study the way in which photographic portraits and urbanity handbooks act in a society in which social and economic differences and distances have undergone a great upheaval since the independence process.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (International library of visual culture ; 27, 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Critical media studies, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

A telenovela brasileira: do nacionalismo à exportação - Santos, Lidia (Caravelle. Cahiers du monde hispanique et luso-brésilien, 2000)
Rentable produit d'exportation diffusé dans 128 pays, le feuilleton télévisé brésilien fait partie du quotidien de la population depuis une trentaine d'années. Si une grande part de son succès repose sur l'exploitation de « la culture des sentiments », dans sa version la plus moderne, il sait aussi plonger au cœur de la réalité comme l'a démontré entre autres avec brio « Le roi du troupeau » (1986) qui mettait en scène le conflit entre les sans-terre et les grands propriétaires terriens.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)